SUSTAINABLE TOURISM MANAGEMENT STRATEGIES FOR COASTAL, ISLAND, AND HIGHLAND ECOSYSTEMS: A CASE STUDY OF BARRU REGENCY - Syamsiah; Andi Rachmat (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal